Soil properties and quinoa yield as affected by irrigation and vermicompost application under a drip-tape irrigation system - Sanandaji, Diba Sheykhi; Heidari, Gholamreza; Fathi, Parviz; Khodaverdiloo, Habib; Sharifi, Zahed (Frontiers in Sustainable Food Systems, 2024)
Quinoa a crop with high nutritional value has the widespread adaptability to different climates and there is an increased demand for this product in the world. In order to reduce chemical fertilizers consumption through using organic fertilizers a two-year study was conducted at the Research Farm of the University of Kurdistan, Iran, during the 2021-2022 growing seasons. In this study the effects of varying levels of irrigation and vermicompost application on soil characteristics and quinoa (Chenopodium quinoa) yield were investigated. The experiments were arranged as split plots within a randomized complete block design. The main factor consisted of four irrigation levels (50%, 75%, 100%, and 125% of quinoa's water requirement), while the sub-factor encompassed four vermicompost application rates (0, 5, 10, and 15 tons per hectare). The irrigation method employed was a drip-tape irrigation system with a seven day interval between irrigations, and water quantities were measured using a volumetric meter on the main pipeline. The results demonstrated that the highest levels of available soil phosphorus (21.83 mg kg -1 ) and soil ammonium (36.08 mg kg -1 ) were observed in the treatment receiving 50% of quinoa's water requirement combined with 15 tons per hectare of vermicompost. Additionally, the application of 15 tons per hectare of vermicompost led to the highest concentrations of soil nitrate (14.16 mg kg -1 ), available potassium (144.62 mg kg -1 ), and quinoa seed yield (1784.01 kg ha -1 ). Over both years, the greatest activity of alkaline and acid phosphatase enzymes was noted in the treatment receiving 125% of quinoa's water requirement in combination with 15 tons per hectare of vermicompost. Vermicompost application was found to enhance yield and ameliorate drought stress by enhancing soil physical and chemical properties and improving soil moisture retention.